Laughing at religious radicalism: How memes promote interfaith, multiculturalism and nationalism - Dewi, Ambar Sari; Sujibto, B. J. (Universitas Trunojoyo Madura, 2024)
Memes have become an important medium for expressing multiple intentions on the internet. Social media has advanced increasingly, making memes a contestation zone, an active hook for delivering information, and an expression of counterradicalism. Memes are a very effective way to take a jab at radicalism in a laid-back or even humorous manner so the public can refreshingly capture the messages. As a part of the digital way, the counterradical group also benefits from the same medium and feature. This research aims to investigate the data on the field on how the memes spreading on social media fight against radicalism in their ways. Therefore, the antiradicalism movement through memes is conducted to look for the patterns, forms, and meanings, especially on X and Instagram accounts of NU Garis Lucu (NUGL) and Muhammadiyah Garis Lucu (MuGL). Using a qualitative approach with the content analysis method, the memes posted in the two accounts were collected between August and December 2022. We found that NUGL and MuGL are actively plotting the antiradicalism movement by criticizing radicalism and fighting against religious indoctrination. Apart from that, for those two accounts, memes function as a medium to raise awareness on multiculturalism and nurture nationalism.